Tissue blood flow and distribution of cardiac output in cats: Changes caused by intravenous infusions of histamine and histamine receptor agonists - Johnston, Barbara M. (1977)
1 The effects of infusions of histamine on blood pressure, cardiac output, heart rate, total peripheral resistance, stroke volume and tissue blood flow have been determined in anaesthetized cats using radio-active microspheres to measure cardiac output and tissue blood flow. 2 Histamine caused dose-dependent falls in blood pressure and total peripheral resistance over the dose-range 1 × 10(-8) to 3.3 × 10(-7) mol kg(-1) min(-1). Histamine had no effect on cardiac output, heart rate or stroke volume. 3 Histamine caused vasodilatation in the heart and stomach, with increased blood flow through these organs, and in the small and large intestine where blood flow was maintained despite the falls in arterial blood pressure. Blood flow to the brain, kidneys, liver, adrenal glands, skeletal muscle, spleen and skin was reduced when arterial blood pressure fell. Vascular resistance increased in the skin and spleen, presumably due to reflex vasoconstriction when blood pressure fell. 4 The selective H(1)-receptor agonist 2-(2-aminoethyl)pyridine lowered blood pressure and decreased total peripheral resistance but did not change cardiac output, heart rate or stroke volume. 2-(2-Aminoethyl)pyridine caused vasodilatation in the heart, small and large intestine and kidneys. Vascular resistance was increased in the spleen and skin. 5 The selective H(2)-receptor agonist 4-methylhistamine also lowered blood pressure and decreased total peripheral resistance but did not change cardiac output, heart rate or stroke volume. 4-Methylhistamine caused vasodilatation in the heart, stomach, small and large intestines and skeletal muscle. Vascular resistance was increased in the skin.